Type 3 Muscarinic Receptors Contribute to Clearance of Citrobacter rodentium. Issue 8 (August 2015) - McLean, Leon P.; Smith, Allen; Cheung, Lumei; Sun, Rex; Grinchuk, Viktoriya; Vanuytsel, Tim; Desai, Neemesh; Urban, Joseph F.; Zhao, Aiping; Raufman, Jean-Pierre; Shea-Donohue, Terez
Abstract : Background: The role of muscarinic receptors in mucosal homeostasis, response to enteric pathogens, and modulation of immune cell function is undefined. Methods: The contribution of type 3 muscarinic receptors (M3R) to mucosal homeostasis within the colon and host defense against Citrobacter rodentium was determined in uninfected and C. rodentium –infected WT and M3R-deficient ( Chrm3 −/− ) mice. In addition, WT and Chrm3 −/− bone marrow-derived macrophages were studied to determine the ability of M3R to modulate macrophage phenotype and function. Results: In Chrm3 −/− mice, clearance of C. rodentium was delayed despite an amplified TH 1/TH 17 response. Delayed clearance of C. rodentium from Chrm3 −/− mice was associated with prolonged adherence of bacteria to colonic mucosa, decreased goblet cell number, and decreased mucin 2 gene expression. Treatment of bone marrow-derived macrophages with bethanechol, a muscarinic-selective agonist, induced a classically activated macrophage phenotype, which was dependent on M3R expression. Chrm3 −/− bone marrow-derived macrophages retained their ability to attain a classically activated macrophage phenotype when treated with the TH 1 cytokine IFN-γ. Conclusions: In Chrm3 −/− mice, mucin production is attenuated and is associated with prolonged adherence of C. rodentium to colonic mucosa. The immune response, as characterized by production of TH 1/TH 17 cytokines, in C. rodentium –infected Chrm3 −/− mice is intact. In addition, M3R activity promotes the development of classically activated macrophages. Our data establish a role for M3R in host defense against C. rodentium through effects on goblet cell mucus production and in the modulation of macrophage phenotype and function. Abstract : Article first published online 15 May 2015.Supplemental Digital Content is Available in the Text.